2001
DOI: 10.1248/bpb.24.1454
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the Neurotoxicity of the Amyloid .BETA. Protein by Genipin.

Abstract: It is now generally documented that the cause of Alzheimer's disease is progressive deposition (histopathologically identified as senile plaque) of the amyloid b protein (Ab) (Ab1-42 and Ab1-40) with aging or due to genetic background in vulnerable brain regions, including the hippocampus and cortex. This deposition is strongly suspected to contribute to disruption of the neuronal network as a result of ubiquitous apoptotic cell death induced by Ab.1,2) The addition of Ab and its hydrophobic core fragments suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 13 publications
1
46
1
Order By: Relevance
“…Fifty and 100 mM of geniposide completely blocked neuronal cell death in granular cell layer. Although Yamazaki et al reported that geniposide could not protect hippocampal cells against b-amyloid-induced toxicity, 7) we found that geniposide attenuated cell death in OGD-exposed rat hippocampal slice culture. This discrepancy suggests the mechanism by which OGD induces cell death is different from cell death by b-amyloid.…”
Section: Resultscontrasting
confidence: 90%
“…Fifty and 100 mM of geniposide completely blocked neuronal cell death in granular cell layer. Although Yamazaki et al reported that geniposide could not protect hippocampal cells against b-amyloid-induced toxicity, 7) we found that geniposide attenuated cell death in OGD-exposed rat hippocampal slice culture. This discrepancy suggests the mechanism by which OGD induces cell death is different from cell death by b-amyloid.…”
Section: Resultscontrasting
confidence: 90%
“…14) It has been suggested that one of the common mechanisms between serum deprivation-and β-amyloid peptide-induced cytotoxicity is the induction of oxidative stress. 15,16) Thus, genipin may suppress the cytotoxicity involved in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that geniposide activates GLP-1Rs, which then protects against Aβ-induced neurotoxicity by the regulation of the expression of IDE in cortical neurons. The cultured hippocampal neurons had significantly degenerated after treatment with Aβ 25-35 , but the degeneration did not occur to the same extent in the presence of genipin (Yamazaki et al, 2001b). One study found that genipin suppressed apoptosis in cultured cells via the inhibition of caspase activation and mitochondrial function (Yamamoto et al, 2000).…”
Section: Possible Neuroprotective Mechanisms In Ad Geniposide Reducesmentioning
confidence: 99%